Numerical determination of the stability of fishing vessels - Acosta Pastor, Victor N. (2000)
It is well known that stability is the most important safety requirement for ships. One must have good information about the stability of the ship in the preliminary design phase to reduce risks. The initial stability of the ship is an important criterion and can be closely evaluated in terms of the shape parameters and the vertical center of gravity. In this study, using some ship data, approximate formulations are deduced through regression analysis for calculations expressed in terms of the ship's preliminary design parameters that can easily provide the approximate GM calculations. Thus designers can provide the stability of the ship in the preliminary design phase and also a set of appropriate design parameters to improve the stability of the ship that can be easily determined.